Early placement of dental implants in maxillary sinus grafted with leukocyte and platelet-rich fibrin and deproteinized bovine bone mineral - Pichotano, Elton Carlos [UNESP]; de Molon, Rafael Scaf [UNESP]; de Paula, Luiz Guilherme Freitas; de Souza, Ricardo Violante; Marcantonio, Elcio [UNESP]; Zandim-Barcelos, Daniela Leal [UNESP] (American Academy of Implant Dentistry, 2018)
This case report aimed to describe the effects of leukocyte and platelet-rich fibrin (L-PRF) associated with demineralized bovine bone mineral (DBBM) and absorbable collagen membrane (CM) on bone regeneration in maxillary sinus augmentation. A 59-year-old Male patient was referred to the Department of Periodontology for implant rehabilitation of his edentulous upper jaw. The treatment plan involved maxillary sinus augmentation followed by implant installations. A split-mouth design was employed in which the right maxillary sinus was filled using L-PRF, DBBM, and CM; the left side was filled with DBBM and CM. After 4 and 8 months postoperatively, 2 dental implants were installed in each of the right and left maxillary sinuses. Cone-beam computerized tomography (CBCT) was taken before and after sinus augmentation for evaluation of tridimensional bone volume alterations. Bone biopsies were harvested from the implant sites for histomorphometric evaluation. Resonance frequency analysis was employed immediately after implant placement and before prosthetic rehabilitation for evaluation of implant stability. Implants were loaded 10 months after sinus augmentation. CBCT analysis showed a higher resorption rate in the right side of the maxillary sinus (L-PRF þ DBBM) compared to the left side (22.25% and 8.95%, respectively). Implant stability quotients were above 68 in all time-points for both groups. Histomorphometric analysis showed a high amount of newly formed bone when L-PRF was used compared with DBBM alone (2 118 102 and 975 535 mm 3 , respectively). Taken together, both techniques were effective for maxillary sinus augmentation, however the addition of L-PRF to the graft allowed early implant placement and accelerated bone healing in the conditions studied.
Keywords: Alveolar bone; Cone-beam computed tomography; Dental implants; Platelet-rich plasma; Sinus floor augmentation